PENGARUH ORIENTASI PASAR TERHADAP PENANGANAN PASCA PANEN BUNGA POTONG KRISAN DI DESA KENTENG, KECAMATAN BANDUNGAN, KABUPATEN SEMARANG - Damara Dinda Nirmalasari Zebua; Sony Heru Priyanto (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2017)
Chrysanthemum in Kenteng Village was conducted at Kenteng Village, Bandungan District, Semarang Regency on 12 February 2016-13 April 2016. This study aims to 1) determine the condition of the chrysanthemum farmers’ market orientation; 2) know the determinants of market orientation of chrysanthemum businessman; and 3) the effect of market orientation on postharvest handling of chrysanthemum. In this study, 100 respondents were choosen to fill in questionnaire which is then analyzed using descriptive statistics and test SEM through IBM AMOS v.22 program. The results show that 1) the orientation on the customer to produce a quality cut flower chrysanthemum is the orientation of the most widely adopted by farmers. Farmers also take the positive things that other farmers do to repair the cut flower chrysanthemum produces, farmers give bonuses to regular customers who buy in large quantities and serve payment in cash receipt, and prioritize what the customer wants and needs and trying to fulfill compared to prioritize short-term profitability; 2) the three determining factors namely age, education and gender, gender can only be accepted as a determinant factor of market orientation. Ownership of market orientation by farmers comes from the demands of the market (brokers, traders and florist) and consumers (decorater); and 3) market orientation has positive influence on post-harvest handling of cut flower chrysanthemum, where the demands of customers on a good cut flower chrysanthemum, attractive, has a shelf life and optimum freshness make farmers give more attention to post harvest activities.